Drug residues in foods : pharmacology, food safety, and analysis - Botsoglou, Nikolaos A., 1946- (Food science and technology (Marcel Dekker, Inc.) ;, 2001)
This text presents data on the physiochemical properties, functions and metabolism, toxicological and pharmacological effects, regulatory control, antimicrobial resistance, and consumer perceptions of food residue regulation.